Persistent Orofacial Pain Attendances at General Medical Practitioners. (February 2023) - Currie, C.C.; Palmer, J.; Stone, S.J.; Brocklehurst, P.; Aggarwal, V.R.; Dorman, P.J.; Pearce, M.S.; Durham, J.
Patients with persistent orofacial pain (POFP) can go through complex care pathways to receive a diagnosis and management, which can negatively affect their pain. This study aimed to describe 44-y trends in attendances at Welsh medical practices for POFP and establish the number of attendances per patient and referrals associated with orofacial pain and factors that may predict whether a patient is referred. A retrospective observational study was completed using the nationwide Secure Anonymised Information Linkage Databank of visits to general medical practices in Wales (UK). Data were extracted using diagnostic codes ("Read codes"). Orofacial and migraine Read codes were extracted between 1974 and 2017. Data were analyzed using descriptive statistics and univariate and multivariable logistic regression. Over the 44-y period, there were 468, 827 POFP and migraine diagnostic codes, accounting for 468, 137 patient attendances, or 301, 832 patients. The overall attendance rate was 4.22 attendances per 1, 000 patient-years (95% confidence interval [CI], 4.21–4.23). The attendance rate increased over the study period. Almost one-third of patients ( n = 92, 192, 30.54%) attended more than once over the study period, and 15.83% attended more than once within a 12-mo period. There were 20, 103 referral codes that were associated with 8, 183 patients, with over half these patients being referred more than once. Odds of receiving a referral were highest in females (odds ratio [OR], 1.23; 95% CI, 1.17–1.29), in those living in rural locations (OR, 1.17; 95% CI, 1.12–1.22), and in the least deprived quintile (OR, 1.39; 95% CI, 1.29–1.48). Odds also increased with increasing age (OR, 1.03; 95% CI, 1.03–1.03). The increasing attendance may be explained by the increasing incidence of POFP within the population. These patients can attend on a repeated basis, and very few are referred, but when they are, this may occur multiple times; therefore, current care pathways could be improved.